The Effect of Emotional Distraction on Declarative Memory and an Exploration of its Physiological Marker: An Affective Computing Perspective - Zulfikri Khakim; Sri Kusrohmaniah (Faculty of Psychology, Universitas Gadjah Mada, 2022)
One of the advantage of e-learning method is the flexibility of embedding audio-visual materials, however whether this goal-irrelevant stimuli would distract the users instead and hinder their performance is generally unknown. The present study aimed to investigate the effects of emotional distraction (ED) on the declarative memory performance. The study was conducted using the within-subject experiment on 38 students aged 18-21 years (20 males). Declarative memory was measured using a Word-Pair Association (WPA) task. ED is given using the International Affective Pictures System (IAPS) and International Affective Digitized Sounds (IADS) grouped based on their valence (neutral, positive, and negative). Measurement of physiological responses was done by measuring Galvanic Skin Responses (GSR), and Electroencephalography (EEG) with Frontal Alpha Asymmetry (FAA) index. Result: significant difference on the WPA score of which Positive is lower than Neutral condition (p = 0.011), but only on the group which the positive block were presented first. From the GSR data, significant main effect of the order of experimental block regardless of the ED valence (p < 0.001; F = 16.045), the first block elicits significantly higher GSR amplitude compared to second (p < 0.001; t = 4.94) and third (p = 0.001; t = 3.90). Meanwhile, the FAA index showed no significant difference (p = 0.654; F = 0.433).